Retaining learners by establishing harmonious relationships in e-learning environment. Issue 1 (2nd January 2019) - Luo, Nuan; Zhang, Yan; Zhang, Mingli
ABSTRACT: Drawing from social resource-social capital theory, this paper aims to clarify and characterize the role of harmonious learner–instructor and learner–learner relationships in promoting experience and retaining learners in online learning environments. Hypotheses are tested by applying a structural equation model and the data are collected from a survey of online learning website ( n = 539). The results suggest that harmonious relationships have a positive impact on learners' experience (i.e. perceived performance, enjoyment and social presence), which, in turn, strengthen learners' continuous intention to use the e-learning platform. And learners' expertise moderates the relationships between harmonious relationships and learner experience. Based on the analysis results, this study can provide educational institutions with useful tactics to retain learners in the e-learning environments.